PERAN GENDER, KONTRIBUSI EKONOMI PEREMPUAN, DAN KESEJAHTERAAN KELUARGA PETANI HORTIKULTURA - Puspitasari, Novi; Puspitawati, Herien; Herawati, Tin (Jurnal Ilmu Keluarga dan Konsumen, 2013)
This research was to analyze the role of gender, women's economic contribution, and family welfare of horticulture families in Sindangjaya village, Cianjur District, West Java Province. This research involved 30 families that chosen purposively and collecting data was held by interview. Gender roles consist of gender roles in domestic, public, and farm financial management activities. Economic contribution was measured by the proportion of women income in family income. Objective well-being was measured by poverty line of BPS and subjective well-being was measured by wife’s satisfaction. Data was analyzed by descriptively and Pearson correlation test. The results showed that gender roles in domestic and public activities in moderate category and gender roles in farm financial management in high category. Average of women's economic contribution in family income was 11,3 percent. Mostly family were nonpoor families base on BPS indicator and also had subjective well-being in moderate category. Women's economic contribution was correlated significantly with objective and subjective well-being.